ESTABLISHING SOLAR GREENHOUSE KILN DRYING SCHEDULES FOR TWO THICKNESSES OF EUCALYPTUS CAMALDULENSIS DEHN. LUMBER IN THE GOVERNORATE OF DOHUK, IRAQ - TAHA, MOHAMMEDAMIN YASEEN (Journal of Duhok University, 2023)
Though its greenhouse solar kiln drying qualities are unknown in Iraq’s Kurdistan region, Eucalyptus (Eucalyptus camaldulensis Dehn.) trees are used in the world’s wood industry. A lack of knowledge about the drying characteristics of these species may result in value losses during drying. After being sawed into flat-sawn and quarter-sawn boards and dried using various drying schedules, the dried board was evaluated by the European Drying Group (EDG) Standards. The results show that drying 50 mm thick samples from 55% moisture content (MC) to 14% at an initial relative humidity of 95% and temperature of 35°C took around 94 days. The second drying cycle was finished at the following temperature and a drying gradient value of 1.6: The 25 mm thick board required a total of (94) days to dry out from 60% to 8% at the same beginning relative humidity rate and temperature. After that, the study’s boards were separated into groups based on their drying quality, with quarter-sawn boards obtaining the best quality and the fewest defects, including mild collapse, low end-split, low bow, cup, and twist, as well as moderate case-hardening